Predictors of concentrations of hexachlorobenzene in human adipose tissue: A multivariate analysis by gender in Southern Spain - Arrebola, J.P.; Martin-Olmedo, P.; Fernandez, M.F.; Sanchez-Cantalejo, E.; Jimenez-Rios, J.A.; Torne, P.; Porta, M.; Olea, N. (Environment international, 2009)
Hexachlorobenzene (HCB) was measured in adipose tissue intraoperatively collected from 387 subjects over 16 years old undergoing surgery in two hospitals in Granada (Southern Spain). HCB was quantified in 90.7% of subjects. The concentrations and frequencies of HCB were similar to those reported in adipose tissue samples in other recent European studies. Exposure patterns differed between females and males: higher HCB concentrations were found in females than in males (geometric mean 18.3 vs. 6.8 ng/g, p < 0.001). The relationship between HCB concentrations and exposure risk factors was assessed by multivariate analysis stratifying by gender. In men, HCB concentrations were predicted ( r 2 = 0.45) by age, body mass index (BMI), place of residence, smoking, consumption of fish, chicken and cheese, occupation related to agriculture, and family involvement in construction activities. In women, HCB concentrations were predicted ( r 2 = 0.50) by age, BMI, consumption of milk and cheese, and occupation related to industry. The finding that women had three-fold higher levels of HCB than the men deserves further investigation.